Suicidal Risk Factors and Youth Population: A Study on Bangladeshi Urban and Rural areas Perspective. - Akter, Jesmin; Mahamud, Akash; Chineta, Okoye Maureen; Lahinta, Ayu Novianti; Shaoan, Md Mirajur Rhaman (Journal of Ecohumanism, 2024)
Suicide is an urgent matter of public health that presents a substantial peril to young populations worldwide. This research aims to conduct a comprehensive overview of the risk factors linked with Suicide among the young population in Bangladesh. Understanding these risk factors could expand targeted prevention strategies and interventions to tackle the issue and endorse mental health. This study utilized quantitative research with a survey questionnaire design to collect data from 764 close family members who committed suicide. The data were randomly selected from Dhaka and Jhenaidah districts in Bangladesh. The study revealed that aged 23-25 years have a higher risk for Suicide, where females 62.96% are at higher risk than males 37.04%. The result finds a significant relationship between family and social environment risk factors. Further findings show that education, married status, family size, and monthly family income variables have various degrees of effect on suicide risk among young people based on their age. Despite the inherent limitations of national surveillance in this study, the research findings catalyze further investigation into delineating specific suicide risk factors. Such endeavors aim to mitigate suicidal behaviors and foster positive psychological development across the lifespan.